TRAF2 and TRAF5 associated with the signal transducing receptor gp130 limit IL-6-driven transphosphorylation of JAK1 through the inhibition of proximal JAK–JAK interaction - Kimura, Masanobu; Nagashima, Hiroyuki; Okuyama, Yuko; Ishii, Naoto; So, Takanori (International immunology, 2018)
TRAF-family members prevent IL-6R-mediated JAK-JAK interaction Abstract Tumor necrosis factor receptor-associated factor 2 (TRAF2) and TRAF5 constitutively bind to glycoprotein 130 kDa (gp130) and inhibit IL-6-driven activation of signal transducer and activator of transcription 3 (STAT3) in CD4+ T cells, which limits the differentiation of pro-inflammatory IL-17-producing helper T cells that require IL-6-receptor (IL-6R) signals for their development. However, it is not known how the interaction between TRAF and gp130 negatively regulates STAT3 activity in the IL-6R complex. We hypothesized that TRAF proteins associated with gp130 might limit the activation of Janus kinase that is needed for the activation of STAT3. To test this, we transfected HEK293T cells to express gp130 and TRAF2 or TRAF5 together with two chimeric JAK1 proteins combined with either the N-terminal or the C-terminal protein fragment of firefly luciferase. Using this luciferase fragment complementation system, we found that the recovery of luciferase enzyme activity was coincident with proximal JAK1–JAK1 interaction and phosphorylation of JAK1 in the IL-6R complex and that the expression of TRAF protein significantly inhibited the recovery of luciferase activity. The binding of TRAF to gp130 via the C-terminal TRAF domain was essential for the inhibition. In accordance with this, upon stimulation of endogenous gp130 with a complex of IL-6 and IL-6R, Traf5−/− CD4+ T cells displayed significantly higher amounts of phosphorylated JAK1 than did their wild-type counterparts. Therefore, our results demonstrate that gp130-associated TRAF2 and TRAF5 inhibit the interaction between two JAK proteins in the IL-6R complex that is essential for initiating the JAK-STAT signaling pathway.